Lemur tail kinase 1 (LMTK1) regulates the endosomal localization of β-secretase BACE1. (15th September 2021) - Komaki, Keisuke; Takano, Tetsuya; Sato, Yutaka; Asada, Akiko; Ikeda, Shikito; Yamada, Kaoru; Wei, Ran; Huo, Anni; Fukuchi, Aoi; Saito, Taro; Ando, Kanae; Murayama, Shigeo; et al.
Abstract: Lemur tail kinase 1 (LMTK1), previously called apoptosis-associated tyrosine kinase (AATYK), is an endosomal Ser/Thr kinase. We recently reported that LMTK1 regulates axon outgrowth, dendrite arborization and spine formation via Rab11-mediated vesicle transport. Rab11, a small GTPase regulating recycling endosome trafficking, is shown to be associated with late-onset Alzheimer's disease (LOAD). In fact, genome-wide association studies identified many proteins regulating vesicle transport as risk factors for LOAD. Furthermore, LMTK1 has been reported to be a risk factor for frontotemporal dementia. Then, we hypothesized that LMTK1 contributes to AD development through vesicle transport and examined the effect of LMTK1 on the cellular localization of AD-related proteins, amyloid precursor protein (APP) and β-site APP cleaving enzyme 1 (BACE1). The β-cleavage of APP by BACE1 is the initial and rate-limiting step in Aβ generation. We found that LMTK1 accumulated BACE1, but not APP, to the perinuclear endosomal compartment, whereas the kinase-negative(kn) mutant of LMTK1A did not. The β-C-terminal fragment was prone to increase under overexpression of LMTK1A kn. Moreover, the expression level of LMTK1A was reduced in AD brains. These results suggest the possibility that LMTK1 is involved in AD development through the regulation of the proper endosomal localization of BACE1. Graphical Abstract: